Determination of carotid disease with the application of STFT and CWT methods - Hardalac, Firat; Yildirim, Hanefi; Serhatlioglu, Selami (Pergamon-Elsevier Science Ltd, 2007)
In this study, Doppler signals were recorded from the output of carotid arteries of 40 subjects and transfer-red to a personal computer (PC) by using a 16-bit sound card. Doppler difference frequencies were recorded from each of the subjects, and then analyzed by using short-time Fourier transform (STFT) and the continuous wavelet transform (CWT) methods to obtain their sonograms. These sonograms were then used to determine the relationships of applied methods with medical conditions. The sonograms that were obtained by CWT method gave better results for spectral resolution than the STFT method. The sonograms of CWT method offer net envelope and better imaging, so that the measurement of blood flow and brain pressure can be made more accurately. Simultaneously, receiver operating characteristic (ROC) analysis has been conducted for this study and the estimation performance of the spectral resolution for the STFT and CTW has been obtained. The STFT has shown a 80.45% success for the spectral resolution while CTW has shown a 89.90% success. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Doppler signal; signal analysis; carotid artery; carotid disease; sonogram; short-time Fourier transform (STFT); the continuous wavelet transform (CWT); receiver operating characteristic (ROC) curve